Unique lingual expression of the Hedgehog pathway antagonist Hedgehog‐interacting protein in filiform papillae during homeostasis and ectopic expression in fungiform papillae during Hedgehog signaling inhibition. Issue 7 (18th February 2022) - Kumari, Archana; Li, Libo; Ermilov, Alexandre N.; Franks, Nicole E.; Dlugosz, Andrzej A.; Allen, Benjamin L.; Mistretta, Charlotte M.
Abstract: Background: Hedgehog (HH) signaling is essential for homeostasis in gustatory fungiform papillae (FP) and taste buds. However, activities of HH antagonists in these tissues remain unexplored. We investigated a potential role for HH‐interacting protein (HHIP), an endogenous pathway antagonist, in regulating HH signaling during taste organ homeostasis. We found a restricted pattern of Hhip ‐expressing cells in the anterior epithelium of each nongustatory filiform papilla (FILIF) only. To test for roles in antagonism of HH signaling, we investigated HHIP after pathway inhibition with SMO inhibition via sonidegib and Smo deletion, Gli2 deletion/suppression, or with chorda tympani/lingual nerve cut. Results: In all approaches, the HHIP expression pattern was retained in FILIF suggesting HH‐independent regulation of HHIP. Remarkably, after pathway inhibition, HHIP expression was detected also in the conical, FILIF‐like atypical FP. We found a close association of de novo expression of HHIP in atypical FP with loss of Gli1 +, HH‐responding cells. Further, we report that PTCH1 is another potential HH antagonist in FILIF that co‐localizes with HHIP. Conclusions: After HH pathway inhibition the ectopic expression of HHIP correlates with a FILIF‐like morphology in atypical FP and we propose that localized expression of the HH antagonist HHIP regulates pathway inhibition to maintain FILIF during tongue homeostasis. Key Findings: Unique and restricted expression of Hedgehog antagonist, HHIP in filiform papillae. Ectopic HHIP expression after Hedgehog signaling inhibition. Cell type‐specific regulation of core Hedgehog pathway components in the adult tongue. Ptch1 emerged to have dual role: Hedgehog receptor in fungiform papillae and Hedgehog antagonist in filiform papillae.